An Overview of Ocular Transmission as Alternative Route Transmission Coronavirus Disease 2019 (COVID-19): Literature Review - Ahmad Rizki Nur Hakiki; Siswoyo; Jon Hafan Sutawardana; Murtaqib; Rismawan Adi Yunanto (Nursing and Health Sciences Journal (NHSJ), 2023)
Coronavirus Disease 2019 (COVID-19) becomes a health crisis in the world. The main route of spreading COVID-19 is through the respiratory tract, but this virus also spread through extra respiratory route. This literature review aimed to describe the ocular transmission as an alternative route of COVID-19 transmission. This literature review study used sources of article obtained through ProQuest, Springer, ScienceDirect, PubMed, and Google Scholar with range 2019-2020 publication years and were traced using a combination of search term for ocular transmission, virus receptor, eye manifestation and COVID-19. Previous research used Experimental design, Case study, and Cross-sectional study, and published from 2019 to 2020. Then analyzed by PRISMA diagram method with four stages starting from identification, screening, eligibility, and included. 4 articles used Experimental study design, 4 articles used Cross-sectional study design, and 2 articles used case study design. This study showed that COVID-19 RNA was found on ocular (conjunctiva and cornea) in a low percentage (2.23%-24%). Patients with confirmed COVID-19 could have ocular manifestations. COVID-19 enter the human body through the eye by spike protein binds to eye receptors that are: ACE2, CD147/Basigin/EMMPRIN, TMPRSS2, ANPEP and AGTR2. Then this virus transferred to the respiratory tract through the nasolacrimal duct. The study showed that ocular transmission can be an alternative route of COVID-19 transmission even with a low percentage level, so it is important for health worker to wear eye protector.